An observation of ChatGPT's use in learning object-oriented programming (OOP) - Nordin, Azlin; Salleh, Norsaremah; Handayani, Dini Oktarina Dwi; Hamzah, Mohd Syarqawy; Zainal Azmi, Nurazlin (2025)
This newsletter poster from the KICT Teaching and Learning Exhibition 2025 presents an observation of undergraduate students' use of ChatGPT for learning Object-Oriented Programming (OOP). The primary uses of ChatGPT were explaining OOP concepts (22%), debugging code (21%), and studying for exams (19%), with smaller proportions using it for solving assignments, generating code snippets (both 12%), and other entries (14%). Student perceptions of the tool were overwhelmingly positive, with the majority agreeing or strongly agreeing that ChatGPT enhances their understanding of OOP, improves coding skills, and boosts problem-solving ability, though there was a moderate acknowledgment of potential over-reliance. The findings are intended to raise awareness about the teaching and learning (TNL) opportunities and challenges of this new learning paradigm.